ENVIRONMENTAL PROBLEMS OF GINNERIES AND THEIR SOLUTIONS - Khozhiev A. A; Dadajonov A. K; Khodzhiev A. A. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main goal of the article is to solve the problem of neutralizing dust particles emitted at cotton ginning plants. Waste from enterprises has been studied and classified. Particular attention was paid to the complete cleaning of cotton before primary processing from impurities, which are considered extremely harmful to human health, and a waste-free technology was created. The application of the technology will bring significant economic benefits to the company, eliminate anemia, eye pain, inflammatory diseases of the respiratory tract, skin diseases among workers of cotton ginning factories.